Captain Pug : the dog who sailed the seas - James, Laura, 1979- (Bloomsbury, 2017)
"Pug is going on a seafaring adventure. He's had jam tarts for breakfast. He's wearing a smart sailor suit. There's just one problem. Pug is afraid of the water!"--